2016
DOI: 10.1016/j.jsbmb.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SOST expression using large minigenes reveals the MEF2C binding site in the evolutionarily conserved region (ECR5) enhancer mediates forskolin, but not 1,25-dihydroxyvitamin D3 or TGFβ1 responsiveness

Abstract: Transcribed from the SOST gene, sclerostin is an osteocyte-derived negative regulator of bone formation that inhibits osteoblastogenesis via antagonism of the Wnt pathway. Sclerostin is a promising therapeutic target for low bone mass diseases and neutralizing antibody therapies that target sclerostin are in development. Diverse stimuli regulate SOST including the vitamin D hormone, forskolin (Fsk), bone morphogenic protein 2 (BMP-2), oncostatin M (OSM), dexamethasone (Dex), and transforming growth factor (TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…A number of factors, including OSX and RUNX2, shown in this study, but also vitamin D, TGF and BMPs act through the binding to motifs in the 5' region of the [30,31]. However, elements located distal to the SOST gene, such as the ECR5 sequence included in the so-called Van Buchem´s region, seem to mediate the regulatory effects of factors such as parathryroid hormone and MEF2 on sclerostin production [32] In conclusion, our results confirm that RUNX2 and OSX modulate the transcription of the sclerostin human gene and common RUNX2 polymorphisms may influence bone mass by still unknown mechanisms.…”
Section: Discussionmentioning
confidence: 63%
“…A number of factors, including OSX and RUNX2, shown in this study, but also vitamin D, TGF and BMPs act through the binding to motifs in the 5' region of the [30,31]. However, elements located distal to the SOST gene, such as the ECR5 sequence included in the so-called Van Buchem´s region, seem to mediate the regulatory effects of factors such as parathryroid hormone and MEF2 on sclerostin production [32] In conclusion, our results confirm that RUNX2 and OSX modulate the transcription of the sclerostin human gene and common RUNX2 polymorphisms may influence bone mass by still unknown mechanisms.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, mechanical loading negatively regulates Sost expression by mechanisms that might involve prostaglandin E2 production, nitric oxide, and periostin expression (11;4951). In vitro studies using a reporter construct carrying the proximal Sost promoter also identified forskolin and oncostatin M as potential regulators of Sost expression (52;53). In addition to PTH, other systemic hormones have a strong impact on Sost regulation.…”
Section: Sost/sclerostin Expression and Its Regulationmentioning
confidence: 99%
“…Vitamin D can also regulate Sost expression, although contradictory data has been published. Thus, using Saos-2 cells, Wijenayaka et al showed that 1α,25-dihydroxyvitamin D3 induces the expression of Sost/Sclerostin (57), whereas St John et al found that it decreases the transcriptional activity of the Sost promoter (52). Similarly conflicting clinical data on the effects of vitamin D status on circulating sclerostin levels have been reported (5862).…”
Section: Sost/sclerostin Expression and Its Regulationmentioning
confidence: 99%
“…Having identified that MEF2C is a crucial determinant of osteocytic SOST expression, an obvious question that emerges is whether PTH blocks MEF2C-driven SOST expression. Early studies using heterologous reporter systems suggested that cAMP signaling might regulate MEF2C activity in the setting of the +45 kb SOST enhancer (Leupin et al 2007;St John et al 2015a). In many biologic systems, upstream signals regulate MEF2 transcriptional activity via nucleocytoplasmic shuttling of class IIa HDAC proteins, which serve as potent inhibitors of MEF2-driven gene expression (Haberland et al 2009).…”
Section: Osteocytesmentioning
confidence: 99%